Perlindungan Hukum bagi Nasabah Bank yang dirugikan dalam Transaksi Layanan E-Banking - Ni Made Febby Savitri Dwi Cahyani; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2022)
The presence of e-banking has now made transactions simpler for customers, this is one form of bank motivation for technological developments. Today's modern customers are very close to various technological conveniences, at the same time also coexist with risks that can occur at any time. The risk must be in line with legal certainty relating to the rights of all Indonesian people which must be enforced and fought for in order to implement Article 28D of the 1945 Constitution. Therefore, this research aims to analyze the legal protection arrangements for bank customers in conducting e-banking service transactions and to discuss legal responsibilities bank to customers who are harmed in conducting e-banking service transactions. This research uses a normative method with a legal and conceptual approach. The legal sources of this research consist of primary, secondary and tertiary sources using recording and documenting techniques as data collection techniques. The results of this study describe that bank customers carrying out e-banking transactions have not been supported by a special regulation, customers are still given preventive and repressive protection. The bank's legal responsibility for customers who lose in e-banking transactions will be given compensation if the customer can prove that it is true that the loss occurred as a result of the bank's error. Complaints to the bank either verbally or in writing can be carried out by the customer. Dispute resolution can be done through litigation, non-litigation or LAPS in the financial services sector